RISK FACTORS OF ESOPHAGUS LESIONS IN CHILDREN WITH OVERWEIGHT AND MEASURES OF PROPHYLAXIS - M.I. Dubrovskaya; I.I. Volodina; Yu.G. Mukhina; O.K. Netrebenko ("Paediatrician" Publishers LLC, 2009)
The work studied clinical and morphological peculiarities of esophagus lesions and factors favoring to its development in children with overweight. The vast majority of cases independently of body weight showed disregeneratory and dystrophic lesions of mucous tunic in distal part of esophagus. Morphological signs of reflux esophagitis were detected at 1 cm upper Z line in 78% of children with overweight. The main role in esophagus lesions' forming play such habits as «stress limosis», use of high-calorie nutrition in big single dose in children with overweight and burden family history concerning diseases of gastrointestinal tract and obesity. Such children are characterized by active body weight increase during first year of life. Present study confirms the significance of proper food behavior and healthy nutrition habits forming in children from first months of life. This lay in the base of gastrointestinal system diseases prophylaxis and forming of overweight and obesity in future.Key words: children, reflux esophagitis, overweight, risk factors, prophylaxis.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):125-129)